Risk Tolerance as a Mediation in SME Investment Decisions in Jepara - Diaz Zahra Septina Pratiwi; Mohammad Yunies Edward (Warmadewa Management and Business Journal (WMBJ), 2026)
This study aims to analyze the role of risk tolerance as a mediating variable in the relationship between financial literacy, experienced regret, financial socialization, and investment decisions among SMEs in Jepara. The study involved 300 SMEs selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that financial literacy, experienced regret, and risk tolerance have a positive effect on investment decisions, while financial socialization has no significant effect. Risk tolerance is proven to mediate the effect of financial literacy and experienced regret on investment decisions, but it does not mediate the relationship between financial socialization and investment decisions. These findings highlight the dominant role of internal individual factors in shaping investment decision-making among SMEs.